2024
DOI: 10.1021/acsnano.4c01190
|View full text |Cite
|
Sign up to set email alerts
|

Built-in Electric Field Promotes Interfacial Adsorption and Activation of CO2 for C1 Products over a Wide Potential Window

Xin Zhao,
Qingguo Feng,
Mengjie Liu
et al.

Abstract: The unsatisfactory adsorption and activation of CO 2 suppress electrochemical reduction over a wide potential window. Herein, the built-in electric field (BIEF) at the CeO 2 /In 2 O 3 n−n heterostructure realizes the C 1 (CO and HCOO − ) selectivity over 90.0% in a broad range of potentials from −0.7 to −1.1 V with a maximum value of 98.7 ± 0.3% at −0.8 V. In addition, the C 1 current density (−1.1 V) of the CeO 2 /In 2 O 3 heterostructure with a BIEF is about 2.0-and 3.2-fold that of In 2 O 3 and a physically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…The work collects comparative LSV curves of MoO 2 /NC/Pt-20 before and after 1000 cycles CV with no significant changes from the initial curve, as well as electrochemical change curves at 10 mA·cm –2 to investigate their long-term electrochemical conduct in all-pH and the results showed that it has a strong long-term stability (Figure j–l). Additionally, by observing the SEM images, MoO 2 /NC/Pt-20 after electrocatalytic HER still retained the rod-like morphology with a rough surface (Figure S7) and the XRD patterns after catalysis are identical to the initial, proving that the structure of the post-tested samples remained almost unchanged (Figure S8), further confirming the satisfactory stability of MoO 2 /NC/Pt-20 in all-pH ranges. The CV results suggest that the MoO 2 /NC/Pt-20 catalyst undergoes distinct redox behaviors depending on the pH environment, with comprehensive redox cycling in acid and a more selective reduction-dominated process in neutral and alkaline conditions (Figure S9).…”
Section: Resultsmentioning
confidence: 99%
“…The work collects comparative LSV curves of MoO 2 /NC/Pt-20 before and after 1000 cycles CV with no significant changes from the initial curve, as well as electrochemical change curves at 10 mA·cm –2 to investigate their long-term electrochemical conduct in all-pH and the results showed that it has a strong long-term stability (Figure j–l). Additionally, by observing the SEM images, MoO 2 /NC/Pt-20 after electrocatalytic HER still retained the rod-like morphology with a rough surface (Figure S7) and the XRD patterns after catalysis are identical to the initial, proving that the structure of the post-tested samples remained almost unchanged (Figure S8), further confirming the satisfactory stability of MoO 2 /NC/Pt-20 in all-pH ranges. The CV results suggest that the MoO 2 /NC/Pt-20 catalyst undergoes distinct redox behaviors depending on the pH environment, with comprehensive redox cycling in acid and a more selective reduction-dominated process in neutral and alkaline conditions (Figure S9).…”
Section: Resultsmentioning
confidence: 99%
“…The Co-based spinel oxides have attracted attention owing to their earth abundance, good catalytic activity, and stability for the OER in alkaline media. Tunable charge separation, carrier migration, and variation of the energy band structure could be achieved. , Moreover, by utilizing the steric hindrance of Co-based spinel oxides, the electronic structure of the metal center can be effectively regulated. Herein, Ni x Co 3– x O 4 is utilized as steric hindrance to manipulate the valence electron of the Fe center on Fe–N 4 –C sites to enhance bifunctional oxygen electrocatalysis. The OER stability is 10 times higher than that of pristine Fe 1 /NC in alkaline media.…”
mentioning
confidence: 99%
“…Then a built-in electric field (BIEF) is generated, which further induces the electrons (e − ) and holes (h + ) to separate in a crystal that is excited by external stress, and thus redox reactions occurred with the adsorbed substances on the catalyst surface to effectively degrade organic pollutants. Therefore, the design and construction of piezoelectric catalysts for the generation of BIEF is crucial, 8–10 which requires piezoelectric catalysts with asymmetric crystal structures and flexible shapes. 11–13…”
mentioning
confidence: 99%